Pengaruh Modernisme terhadap Aplikasi Ragam Hias pada Desain Masjid Salman-ITB Karya Ahmad Noe’man - Achmad Haldani Destiarmand (ITB Journal Publisher, LPPM ITB, 2009)
This research will focus on the Ir. Achmad Noe'man perspective symptoms of decoration on the Salman ITB mosque that are designed around 5 (five) decades ago, namely in 1959. Methodologically this study is a descriptive research approach to the Social History of Art. Objects are selected based on observation and the assumption that the role of decoration in the mosque he designed had a very strong reduction compared to the tradition of decorating the mosque during this time both in Indonesia and foreign countries. Ornamental pattern as the heart of Islamic art is not as important anymore in the eyes of the architect. And of course it contains a variety of reasons or background concepts and ideas that cannot be separated from the situation at that time. In Salman mosque seemed how strong the desire of Achmad Noe'man to go with the flow and current popularity of modernism which is too simple and functional, also inspired by the purism, though as a Muslim architect, he has the concept and other perceptions about the value of beauty in a more contemplative and transcendent. That is, although the ideology that is reflected in the Salman mosque is very secular in accordance with the concept of modernism, but Achmad Noe'man not lose power as well as spiritual. From the observations made can be concluded that the spirit factor of the time was very influential towards the constellation of decoration on some modern mosques in Indonesia at that time (Istiqlal, for example), but understanding the sense in the application shift of decoration on the modern mosque's created by Noe'man Achmad means that it also refers to the private contemplation (inner value) which tend to be more stable than the influence of his understanding of the flow of thought, academic factors, political, and spirits that tend to be volatile times like a fashion phenomenon.